The development of care model for continuous ambulatory peritoneal dialysis patients by using the primary nursing system in Suratthani Hospital - Nilphat, Thassana; Lawanasakol, Siriporn; Lertpiyathanaku, Panida; Eamjanprateep, Sadakarn (Region 11 Medical Journal, 2020)
Background: The process of caring for patients with chronic kidney disease lacked continuity and lacked communication with nurses in ward. The occurrence of complications after discharge of patients for continuous ambulatory peritoneal dialysis (CAPD) at home. Objectives: 1) To develop a model of care for patients undergoing CAPD 2) To examine the effectiveness of used the primary nursing system. Methods: There were 4 phases: 1) situational analysis 2) CAPD Model development 3) Implementation and 4) Evaluation. Participants were 31 registered nurses, 120 CAPD patients undergoing CAPD for at least 6 months. The instruments consisted of 1) Infection record form 2) Interview form for multidisciplinary team 3) Interview form for patients and caregivers 4) test knowledge of nurses 5) patients self-care ability questionnaire 6) satisfaction of nurses’ questionnaire and 7) The 9 Thai quality of life. The instruments were examined for contents validity by the five experts. The validity were 0.77, 0.82, 0.84, 0.83 and the reliability were 0.84, 0.90, 0.85, 0.85, 0.79 respectively. The data were analyzed using descriptive statistics, dependent t-test and Chi-square test. Results: Results found that 1) a care model for CAPD patients using the primary nursing system significantly enhanced nurses' knowledge at a good level (mean=18.03, SD=1.22) (p<0.01). Nurses' satisfaction and Patients' satisfaction were at a good level (mean =3.93; SD=.57) and (mean=4.43; SD=.82); respectively. Selfcare ability of CAPD patients were increasing (p<0.01). The rate of peritonitis and sites of CAPD infection were decreased significant (p<0.01) 6) CAPD patient quality of life was a good level (p<0.01). Conclusion: A care model for CAPD patients using the primary nursing system can be care CAPD patients and can be development to chronic care disease.